การพัฒนารูปแบบกิจกรรมการศึกษานอกระบบโรงเรียนตามแนวคิดนีโอฮิวแมนนิส เพื่อเสริมสร้างการเรียนรู้เกี่ยวกับคุณลักษณะที่พึงประสงค์ ของผู้ที่ประสบความสำเร็จตามกฎแห่งความสำเร็จของนโปเลียน ฮิลล์ - วรรัตน์ อภินันท์กูล (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purpose of this research was to develop the non-formal education activity models based on the Neo-Humanist approach to enhance learning about desirable characteristics of a successful person in accordance with Napoleon Hill s law of success. The program and handbook of non-formal education activity were based on the Neo-Humanist approach to enhance learning about desirable characteristics of a successful person in accordance with Napoleon Hill s law of success and were used with 40 students from Faculty of Education, Chulalongkorn University as a sample group. The subjects were divided into 2 groups. Both groups were then divided into the experimental group and the control group with 20 people in each. The experimental group had been participated in this activity which had 2 parts: workshop program for 40 hours and do activities by self-study in handbook for 15 hours. The research results were as follow: 1. process of model such as (1) educational goal setting (2) learning experience selection(3) learning experience organization (4) learning evaluation 2. Summary of model for experimental group was that the posttest learning about desirable characteristics of a successful person of the experimental group was higher than that of the control group significantly at the .05 level.